Double exposure [videorecording (DVD)] - Goldberg, Howard, 1948-; Calvert, Alexander; Cowan, Caylee; Kim, Kahyun (Freestyle Digital Media, 2025)
How does a bride compete with a beautiful influencer who comes back from the dead to steal her husband? The past and present mysteriously collide as a man, in a life and death struggle, combats his guilt over what happened to his first love.